Aktivitas analgesik tanaman gedi (Abelmoschus manihot L.) pada mencit (Mus musculus) - Pratiwi, Elsa Nanda Ayu; I Gusti Ngurah Agung Dewantara Putra; Eka Indra Setyawan (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
Gedi plant (Abelmoschus manihot L. Medik) is a tropical plant of the Malvaceae family which has been known in North Sulawesi as a vegetable plant. Gedi plants have various medicinal benefits, such as antidiabetic, antimicrobial, anticancer, analgesic, antiinflammatory, antioxidant, and antiplasmodial activity. The ethanol extract of Gedi leaf had an analgesic activity which was orally administered in mice and the amount of its writhing is observed after being induced by heat. The data showed that the analgesic effect of Gedi leaf ethanol extract at a dose of 60 mg/30 g BB equivalent to a dose of 2000 mg/Kg BB was greater than the positive control dose or tramadol used. Other research also stated that the petroleum ether and methanol extracts of Gedi leaf showed flavonoids, steroids, and triterpenoids which had anti-inflammatory and analgesic activity. Petroleum ether and methanol extract of Gedi leaf at a dose of 400 mg kg -1 showed a maximum reaction time of 14.1 ± 0.21 and a minimum of 6.98 ± 0.29 which indicates a significant pain threshold.